Effect Of Hydrogen Flow Rate On The Quality Of Carbon Nanotubes Produced Using The Floating Catalyst Chemical Vapor Deposition Method - Raja Othman, Raja Nor Izawati (2007)

(untitled)
Well aligned multi walled carbon nanotubes (MWNTs) was successfully synthesized by floating catalyst chemical vapor deposition method (CVD) involving the catalytic decomposition of benzene upon the surface of iron particle. Two sources of hydrogen were employed and varied; H2* that carried benzene vapor and H2** that supplied fresh hydrogen into the electrical furnace to analyze the effects they had on quantity as well as the morphology and structure of the produced CNTs. Total hydrogen flow rate was kept constant to allow constant residence time. Reaction time was also varied to study the growth rate of the products. The remaining parameters such as reaction temperature (850°C), ferrocene sublimation temperature (120°C), and mass of ferrocene (200 mg) were kept constant throughout the reaction. Argon (300 ml/min flow rate) was flown into the system before reaction to provide an inert atmosphere in the furnace. It was also flown after reaction to prevent product oxidation. The quantity of CNTs produced was highest (0.08g) when the reaction time and supply of benzene were maximized (t = 50 min, H2*=350 ml/min, and H2**= 0 ml/min. The structure of the selected CNT samples was then further characterized via the means of Electron Microscopy (SEM, TEM, and HRTEM) as well as X Ray Diffractometer. By using TEM, measurement of 50 tubes per sample revealed CNTs of outer diameter (OD) from 5 to 55 nm and inner diameter (ID) from 5 nm to 25 nm for all conditions studied. At H2* = 150 ml/min, H2** = 250 ml/min, and t = 50 min, mean OD and ID of 18.64 nm and 4.85 nm with standard deviation of 18.64 nm and 4.85 nm, respectively were obtained. XRD results revealed formation of sharp and narrow peaks at around 26° position (2θ), which confirms the presence of highly crystallized CNTs for all samples. The values of the intershell spacing of the wall (d002) are between 0.338 nm to 0.342 nm. The values of full width at half maximum (FWHM) of the peaks of 0.7144, 0.2273, and 0.0200 was obtained when H2*=350 ml/min, H2*=250 ml/min and H2*=150 ml/min, respectively at 50 min reaction time. The reduction in the FWHM value indicated the CNTs exhibit more crystalline graphite as more H2** was supplied.